Public policy analysis: an integrated approach - Kurebwa, Jeffrey; Mutukwa, William; Chivaku, Shupikai (Sumerianz Publication, 2020)
The book defines and illustrates phases of policy analysis, describe elements of integrated policy analysis, distinguish four strategies of policy analysis, contrast reconstructed logic and logic-in-use, describe the structure of a policy argument and its elements and interpret scorecards, spreadsheets, influence diagrams, decision trees, and argument maps.
Keywords: Public policy; Government; Policy analysis; Public organizations; Land reform policy.